L’entretien des églises parisiennes des XIXe et XXe siècles - Joël Duvignacq; Laurence Fouqueray (In Situ)
The municipality of Paris owns a significant heritage of places of worship comprising 96 buildings all together, 44 of which were built during the 19th century and 10 during the 20th. The article presents an inventory of this ensemble of 54 churches, temples and synagogues, characterising each site’s localisation, the different types of protection that cover it and its chronological evolution. The article then presents the Office of historic places of worship, responsible for these places within the city’s directorate of cultural affairs. The specific skills necessary for this Office’s mission are also examined: in-house skills, skills which are to be found within the directorate and external, specialised skills for which contracts are necessary. There is then an examination of the actual work of maintaining and repairing these places of worship, by looking at how this work is planned under different budgetary headings. These are the ‘places of worship plan’ which sets out criteria for programming restoration work; the ‘non-localised annual provision’, which covers urgent work required by considerations of security or urgent repairs. The office must remain flexible in this respect, capable of intervening anywhere in Paris according to needs. Another budget heading is the ‘annual provision for non-localised security and technical work’ (electricity, heating, measures against theft), and a last one is the annual programme for the restoration of stained-glass windows and organs. The article concludes with an examination of the particularities of this work of maintaining Parisian places of worship. These are presented in brief descriptions based on the daily tasks of the agents who work for the office.